Respostas

2014-03-03T15:22:59-03:00
F(1/3) = 1//1/3 = 3. Temos (x,y) = (1/3,3). f(x)= 1/x implica que f '(x) = - 1/x². Segue que, dy/dx] (1/3,3) = - 1// (1/3)² = -9 = m ( coeficiente angular). Substituindo na expressão que determina a equação, onde temos o ponto (Xo,Yo) = (1/3,3). Assim,
Y - Yo = m ( X - Xo)
Y - 3 = - 9 ( X - 1/3)
Y - 3 = - 9X + 3
Y = - 9X + 6.     

f(3) = 1/3. Temos (x,y) = (3,1/3).f"(x) = - 1/x². Segue que, dy/dx] (3,1/3) = -1/9.
Y - Yo = m (X - Xo)
Y - 1/3 = -1/9(X -3)
Y -1/3 = -X/9 + 3/9
9Y -3 = -X +3
9Y= -X+6
Y = -X/9 +2/3